Geochemical Properties of Fire Opal Occurences in Kütahya (SW Turkey) - TEKBAS CANDAR*, M.; ISLER†, F. (Asian Journal of Chemistry, 2024)
The Simav fire opal occurences have specific characteristics. It hasa variety of appearance micro and nanostructures. Chemical, mineralogicalproperties, optical observation and SEM analyses of Simav fireopal occurences have been investigated. Micromorphology, crystal structure,particle size were examined. To purpose scanning electron microscopesused on microtextures on fire opal. The yellow to brown colour is correlatedwith Fe concentration. The purpose of the peresent investigationsare two fold (1) clarify the microtextures at a level of nanometerscale (2) to analyze the mechanism of their formation.